Enhancing researcher capacity to engage youth in research: Researchers' engagement experiences, barriers and capacity development priorities. (14th March 2020) - Hawke, Lisa D.; Darnay, Karleigh; Relihan, Jacqueline; Khaleghi‐Moghaddam, Mohammad; Barbic, Skye; Lachance, Lisa; Ben‐David, Shelly; Brown, Marion; Iyer, Srividya; Chaim, Gloria; Soklaridis, Sophie; Kidd, Sean A.; et al.
Abstract: Background: There is increasing emphasis on engaging youth in research about youth, their needs, experiences and preferences, notably in health services research. By engaging youth as full partners, research becomes more feasible and relevant, and the validity and richness of findings are enhanced. Consequently, researchers need guidance in engaging youth effectively. This study examines the experiences, needs and knowledge gaps of researchers. Methods: Eighty‐four researchers interested in youth engagement training were recruited via snowball sampling. They completed a survey regarding their youth engagement experiences, attitudes, perceived barriers and capacity development needs. Data were analysed descriptively, and comparisons were made based on current engagement experience. Results: Participants across career stages and disciplines expressed an interest in increased capacity development for youth engagement. They had positive attitudes about the importance and value of youth engagement, but found it to be complex. Participants reported requiring practical guidance to develop their youth engagement practices and interest in a network of youth‐engaged researchers and on‐going training. Those currently engaging youth were more likely to report the need for greater appreciation of youth engagement by funders and institutions. Conclusions: Engaging youth in research has substantial benefits. However, skills in collaborating with youth to design, conduct and implement research have to be learned. Researchers need concrete training and networking opportunities to develop and maximize these skills. They also need mechanisms that formally acknowledge the value of engagement. Researchers and those promoting youth engagement in research are encouraged to consider these findings in their promotion and training endeavours.